A Dêixis na construção de sentidos em comentários alusivos ao nordeste: um estudo enunciativo em sites esportivos e suas implicações no ensino de língua portuguesa. - Correia, Aurineide Profírio Barros (2017)
This work, of qualitative nature, exploratory measures, based on study of case aims to analyze the dêixis in the construction of meaning in comments alluding to the Northeast on sports sites. It is based on the ennunciative perspective of language supported on the theory of Enunciation of Émile Benveniste. To this aim, we examined six comments that allude to the Northeast, running sports sites, watching as the dêiticos elements, in their personal, spatial and temporal levels contribute to the representation of subjectivity in the language, since these elements are interpreted with reference to the situation may include and refer to anything linguistic, not exclusively referring to an object or concept. It is relevant to highlight that Benveniste foccused on a strand of analysis of language in use, in action, in his example, dimension and this peculiarity directed our attention to the implications of this design language in the teaching of Portuguese Language, in which the text assumes an active role of building directions, requiring the interaction of their interlocutors. In this understanding, the design of Benveniste about the study of the language implies a relationship that justifies the use of, or the choice of certain words in speech by a guy, revealing, in your semantic aspect the establishment of the relationship of the signs with the conditions of an utterance, that determines the meaning in the light of oppositions imposed within the linguistic system and outside it. Benveniste stresses the dêixis (personal, spatial and temporal) as explicit brand relative to the subject with the statement, highlighting that these elements relate to the reality of speech and can only be identified in terms of locution, involving the relations of subjectivity that comprise locutor and a alocutario stabilished for him. The analysis of the data revealed that the meaning of an utterance is given by the possibility of sintagmatics choices made by a locutor that appropriates the language and sets out its position of subject when self declares "I" and set up a "you" in a given discursive space and time. Understanding the actions of these brands in the comments analyzed provides a reflection on the language in use and its mediation, providing ways to conceive the language and its methodological implications in the teaching of Portuguese Language.